Inhibition of Nitric Oxide Generation in Mononuclear Splenocytes from Multiple-Low-Dose-Streptozotocin Diabetic Mice - Karabatas, Liliana Margarita (2013)
Mice injected with multiple low dose of streptozotocin (mld-SZ) or transferred with mononuclear splenocytes (MS) from mld-SZ donors constitute animal models that allow the study of autoimmune diabetes. Mld-SZ mice show a progressive beta-cell destruction iniciated during non-specific islet inflammation involving free radicals as nitric oxide (NO°). Pharmacological inhibitors of NO° synthase delay or prevent the outbreak of disease, but have deleterious side effects when administered in vivo. The aim of this study, was to clarify the role of NO° on the ability of MS from mld-SZ mice to impair insulin secretion. Also, we invest igated the beneficial effects of using NO° synthase inhibitors in vitro on anti-beta cells agression. Methods: NO° was measured in cultured MS and islets of Langerhans isolated from mice at days 4 to 16 after the first mld-SZ injection. MS were also cultured with an inhibitor of NO° production, L-NG-monomethyl-arginine (L-NMMA), and then: a) injected in syngeneic mice to evaluate their insulin secretion patterns or b) co-cultured with islet cells to estimate the capacity of MS to exert in vitro cellular immune aggression. Results: Cultured islets of Langerhans and MS from mld-SZ mice showed increases in NO° production (p>0.05). MS from mld-SZ mice, obtained at days 4 to 9 and precultured with L-NMMA showed ameliorations in their deleterious effect on insulin secretion from transferred recipient mice and from cocultured islet cells (p<0.05). Conclusions: These results suggest that the inhibition of NO° production “in vitro” reduced the aggressive capacity of MS from mld-SZ mice avoiding, at least in part, beta cell damage and destruction.